OP0263 Efficacy and safety of GLPG0634, a selective JAK1 inhibitor, after short-term treatment of rheumatoid arthritis; results of a phase IIA trial. (23rd January 2014) - Vanhoutte, F.P.; Mazur, M.; Namour, F.; van der Aa, A.; Wigerinck, P.; van 't Klooster, G.A.E.
Abstract : Background: GLPG0634 is an orally-available, selective inhibitor of Janus kinase 1 (JAK1). JAKs are critical components in signaling pathways for a number of cytokines and growth factors, including those involved in the disease process of rheumatoid arthritis (RA). Other non-selective JAK inhibitors have shown long-term efficacy in RA trials with an early onset of action, but doses and thereby efficacy are limited by side effects. By specifically targeting JAK1, treatment with GLPG0634 is expected to result in a cleaner safety profile while maintaining the rapid onset of clinical efficacy. Objectives: Evaluate the short-term efficacy and safety of GLPG0634 in RA patients with insufficient response to methotrexate (MTX) alone. Methods: A double-blind, placebo-controlled Proof-of-Concept trial in patients with active RA, showing an insufficient response to MTX, was conducted. Twenty-four patients with moderate to severe disease received GLPG0634 200 mg daily, half as once-daily regimen (200 mg q.d.) and half as twice-daily regimen (100 mg b.i.d.), and 12 patients received a matching placebo for a period of four weeks, while continuing to take their stable background therapy of MTX. Results: Patient and disease characteristics were comparable for all three dose groups, with DAS28 (CRP) disease activity scores between 6.3 and 6.6. In each dose group, 11 out of 12 patients were female. The patients were well exposed to GLPG0634, with the same pharmacokinetics as previously observed in healthy volunteers. GLPG0634 was found well tolerated and safe with a rapid onset and high level of efficacy. Considering the small sample size, no clinically relevant differences were observed among the 100 mg b.i.d. and the 200 mg q.d. dose regimens. GLPG0634 met the primary endpoint of significant improvement in ACR20 response rate. Overall ACR20 responses were observed in 83% of patients receiving GLPG0634 vs. 33% of patients receiving placebo (p<0.01). GLPG0634 showed impressive results in secondary efficacy endpoints, such as the DAS28 (-2.5), and in reductions of serum C-reactive protein levels (-24.4 mg/L), both significant changes vs. placebo (p<0.0001). All patients completed the trial and no treatment-emergent safety signals were reported. No severe adverse events were reported in patients receiving GLPG0634. Instead of anemia, a modest improvement in hemoglobin was observed. In contrast to observations with JAK inhibitors with other selectivity profiles, no increases in LDL/cholesterol and no liver effects (ALT/AST) were observed in this trial. Conclusions: These early clinical results are the first to demonstrate that selective inhibition of JAK1 is efficacious and safe for the treatment of RA. Consistent with the lack of inhibition of JAK2, no anemia was observed. Remarkable results include the high level of response within 4 weeks and the absence of effects on LDL/lipid. An extended GLPG0634 dose-range finding trial is now being conducted to further define the optimal doses for efficacy and safety for longer term studies. Disclosure of Interest: F. Vanhoutte Employee of: Galapagos, M. Mazur: None Declared, F. Namour Employee of: Galapagos, A. van der Aa Employee of: Galapagos, P. Wigerinck Employee of: Galapagos, G. Van 't Klooster Employee of: Galapagos